Land Use Negotiation in Eastern Morocco. (11th November 2011) - Kreuer, David
Abstract : In this article, I analyse a steppe region in contemporary Morocco, outlining the political environment in which land use is currently negotiated. I ask what place different actors such as the state, the tribe, or local individuals occupy in the relevant power structures. Relying on recent fieldwork, I then discuss land appropriation by tribal households. Con flict-resolution mechanisms are presented in the third section. My contribution shows that access to land is often related to other types of resources (such as livestock, access to institutions and social prestige), and points out that a detailed, actor-centred analysis is essential to understanding the making of politics in the Moroccan high plateaus.